Peano Axioms.

Axiom 2.1

$0$ is a natural number.

Axiom 2.2

If $n$ is a natural number then $n++$ is also a natural number. (Here $n++$ denotes the successor of $n$ and previously in the book the notational implication has been bijected to the familiar $1,2…$).

Axiom 2.3

$0$ is not the successor of natural number; i.e. we have $n++≠0$ for every natural number $n$.

Axiom 2.4

Different natural numbers must have different successors; i.e., if $n,m$ are natural numbers and $n≠m$, then $n++≠m++$.

Axiom 2.5

Let $P(n)$ be any property pertaining to a natural number $n$. Suppose that $P(0)$ is true, and suppose that whenever $P(n)$ is true, $P(n++)$ is also true. Then $P(n)$ is true for every natural number $n$.

Definition of Addition: Let m be a natural number. We define, $0+m=m$ and suppose we have inductively defined the addtion $n+m$ then we define, $(n++)+m=(n+m)++$. Where $n++$ is the successor of $n$.

Terence Tao has a proof in his Analysis I book, but I couldn't understand . I want a proof line by line like this:

Thm: 3 is a natural number \begin{align*} & 0 \text{ is natural } && \text{Axiom 2.1 }\\ & 0++ = 1 \text{ is natural } && \text{Axiom 2.2}\\ & 1++ = 2 \text{ is natural } && \text{Axiom 2.2}\\ & 2++ = 3 \text{ is natural } && \text{Axiom 2.2} \end{align*}

  • 2
    $\begingroup$ What have you proven so far? Have you shown commutativity? $\endgroup$ – InterstellarProbe Jul 31 '18 at 13:52

The proof is by induction on $a$.

Basis [case with $a=0$]. We want to prove that :

if $0+b=0+c$, then $b=c$.

But we have that : $0+b=b$, by definition of addition.

And also : $0+c=c$.

Thus, by transitivity of equality : $b=c$.

Induction step. Assume that the property holds for $a$ and prove it for $a'$ [I prefer to use $a'$ instead of $a++$ for the successor of $a$].

This means :

assume that "if $a+b=a+c$, then $b=c$" holds, and prove that "if $a'+b=a'+c$, then $b=c$" holds.

We have $a'+b=(a+b)'$ by definition of addition.

And $a'+c=(a+c)’$, by definition of addition.

We assume that : $a'+b=a'+c$, and thus, again by transitivity of equality, we have that : $(a+b)'=(a+c)'$.

By axiom 2.4 (different numbers have different successors), by contraposition, we conclude that $(a+b)=(a+c)$.

Thus, applying induction hypothesis, we have that :


The general strategy used above in order to prove "if $P$, then $Q$", is to assume $P$ and derive $Q$.

This type of proof is called Conditional Proof; we can see it above :

1) if $a+b=a+c$, then $b=c$ --- induction hypothesis

2) $a'+b=a'+c$ --- assumption for CP

3) $(a+b)'=(a+c)'$ --- from 2) and definition of addition and tarnsitivity of equality

4) $a+b=a+c$ --- from 3) and axiom 2.4 by Contraposition [the axiom says : "if $(a+b \ne a+c)$, then $(a+b)' \ne (a+c)'$"; thus, contraposing it we get : "if $(a+b)' = (a+c)'$, then $(a+b) = (a+c)$"] and Modus ponens

5) $b=c$ --- from 4) and 1) by Modus ponens (also called : detachment)

6) if $a'+b=a'+c$, then $b=c$ --- from 2) and 5) by Conditional Proof.

  • 1
    $\begingroup$ (In your last yellow box before the general strategy, it should be $b=c$) $\endgroup$ – Jason DeVito Jul 31 '18 at 14:31
  • $\begingroup$ Thanks! Amazing. $\endgroup$ – Henrique Jul 31 '18 at 15:25

Here is a formal proof done in Fitch:

(Note: I use $s(x)$ instead of $x$++)

enter image description here


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.